What Drives Herbal Traditions? The Influence of Ecology and Cultural Exchanges on Wild Plant Teas in the Balkan Mountains - Mousaab Alrhmoun; Naji Sulaiman; Andrea Pieroni (Land)
This study investigates the ethnobotanical diversity of wild plant teas across various populations in the Balkan mountain regions, focusing on cultural and ecological influences. Data were collected through ethnobotanical field surveys conducted in thirteen distinct areas, encompassing approximately 900 interviews with local populations, including Albanians, Bosniaks, North Macedonians, Goranis, and Serbs. The study identifies 143 genera used in traditional teas, with species frequency and distribution patterns analysed concerning elevation and cultural factors. Statistical analyses using Principal Component Analysis (PCA) and Cluster Analysis revealed clear grouping patterns between populations based on ecological zones. The results show a clear correlation between altitude and the herbal use of plant genera, with higher elevations (above 700 m) supporting a greater variety of local species. Cultural practices, such as tea consumption during communal gatherings, also significantly shaped the selection of plants across different populations. For instance, Sideritis species were most prevalent among Albanian and North Macedonian communities, while Thymus and Mentha species were widely used across all groups. Moreover, cultural exchanges can explain the similarity of wild teas reported by Bosniaks (in Bosnia) and North Albanians, located far away from each other but showing similar traits due to possible common origins or the effect of centuries of pastoralism, which may have generated a constant exchange of local plant practices. The study concludes that ecological conditions and cultural exchanges significantly influence the choice, use, and resilience of wild plant herbal traditions in the Balkans. However, modern pressures such as urbanisation and market-driven consumption are increasingly threatening these practices. This highlights the need for conservation strategies that integrate ecological preservation and cultural heritage safeguarding.